Talk on the Street: The Impact of Good Streetscape Design on Neighbourhood Experience in Low-density Suburbs. Issue 2 (15th March 2021) - Abass, Zainab Ibrahim; Tucker, Richard
ABSTRACT: This paper examines the impact of streetscape design on correlates of social interaction in low-density suburbs. While much research has investigated the impact on social interaction of the physical environment in high-density contexts, few studies have found evidence elucidating how neighbourhood design can improve suburban social interaction. Analyses examined the extent to which three "neighbourhood experience" factors –  Neighbourhood contentment; Active socializing  and  Accessibility  – are impacted by the acceptable provision of some streetscape characteristics. The findings show that neighbourhood experience was significantly different between three suburbs, and that good streetscape design had significantly predicted  Neighbourhood contentment  and  Accessibility,  even when allowing for the interaction of socio-demographic variables. It was also found that social demographic characteristics – in particular length of residence, but also the number of children and income – significantly impact  Active socializing  and have independent influence compared to physical design.